2008
DOI: 10.1007/s00436-008-1264-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of cytosolic and mitochondrial tryparedoxin peroxidase in Trypanosoma cruzi populations susceptible and resistant to benznidazole

Abstract: Antioxidant defense in Trypanosomatids has been indicated as a potential target for chemotherapy. Tryparedoxin peroxidase (TXNPx) participates in this defense by metabolizing hydrogen peroxide to water molecules. In this work, genes encoding both cytosolic (cTcTXNPx) and mitochondrial (mTcTXNPx) TXNPx were characterized in 15 benznidazole-susceptible and resistant Trypanosoma cruzi strains. Northern blot and real-time RT-PCR analyses revealed that the levels of cTcTXNPx and mTcTXNPx mRNA were two-fold higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 41 publications
3
44
0
3
Order By: Relevance
“…66 Many molecular studies have compared those two populations to identify resistance markers. [67][68][69] Although no correlation was detected, other studies have found differences in the in vitroinduced BZ-resistant strains (17WTS X 17LER). 67 More recently, a proteomic analysis of BZS-Y/BZR-Y and 17WTS/ 17LER also identified many overexpressed proteins in the BZR-Y population.…”
mentioning
confidence: 77%
“…66 Many molecular studies have compared those two populations to identify resistance markers. [67][68][69] Although no correlation was detected, other studies have found differences in the in vitroinduced BZ-resistant strains (17WTS X 17LER). 67 More recently, a proteomic analysis of BZS-Y/BZR-Y and 17WTS/ 17LER also identified many overexpressed proteins in the BZR-Y population.…”
mentioning
confidence: 77%
“…In Leishmania donovani, not only is TXNPx crucial for survival during oxidative stress, it also enhances infectivity (69). For Trypanosoma cruzi, there is increasing evidence showing that antioxidant enzymes are critical for immune evasion by protecting the parasite from macrophage-derived reactive oxygen species (ROS) (56). In addition, the expression level of thioredoxin peroxidase (spot 33) (TVAG_484570) increased ϳ1.9-fold.…”
Section: Fig 3 2-de Maps Of Trophozoites and Fn-bound Amoeboid Cells mentioning
confidence: 99%
“…Interestingly, the deletion of copies of genes encoding two different nitroreductases, namely, old yellow enzyme (TcOYE; also named prostaglandin synthase or NADPH oxidoreductase) and trypanosomal type I nitroreductase (NTR-1) (Wilkinson et al, 2008), has been associated with a phenotype of T. cruzi, which is resistant to NFX and BZ in vitro. Overexpression of enzymatic activity related to antioxidant response, like that of tryparedoxin peroxidase, ascorbate peroxidase, and iron-superoxide dismutase, has been detected in T. cruzi populations resistant to BZ (Nogueira et al, 2006(Nogueira et al, , 2009(Nogueira et al, , 2012. In addition, the hexose transporter activity was 40% lower in a BZ-resistant T. cruzi population than in the susceptible control (dos Santos et al, 2012).…”
Section: Introductionmentioning
confidence: 96%